Hajj and the chaos of the Great War: Pilgrims of the Dutch East Indies in World War I (1914-1918) - Frial Ramadhan Supratman (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2020)
The outbreak of World War 1 in 1914 had a major effect on global interactions during the early 20th century. Travel from one country to another to conduct trade, study, research, and religious pilgrimages become disrupted. Hajj (pilgrimage to the holy city of Mecca) is one of the areas affected by the outbreak of this great war. The number of pilgrims from the Dutch East Indies dropped dramatically. Hajj ships also ceased operations. Besides, many Dutch East Indies pilgrims in Mecca were unable to return home and suffered life misery during World War I. This article investigates the impact of World War I (1914-1918) on Dutch East Indies pilgrims. The purpose of this article is to find out how Dutch East Indies Muslims responded to hajj during World War I. In this study, the researcher used historical methods that emphasised the exploration of the sources of Early 20th century Malay and Dutch newspapers. The researcher argues that in line with the events of World War I, the Dutch colonial government still intervened against religious practices in the Dutch East Indies, especially the hajj, thus worsening the situation of the Dutch East Indies pilgrims in Mecca. Opponents of this policy, such as R.A.A. Djajadiningrat, Hasan Mustapa, Cokroaminoto, Tafsir Anom, and Rinkes, formed the Hajj Assistance Committee to help pilgrims return to the Dutch East Indies.